Pemanfaatan buah andaliman (Zanthoxylum acanthopodium) dari Dataran Tinggi Gayo dalam pembuatan krim antibakteri - Miftahurrahman Miftahurrahman; Teuku Khaiyir Raqi Ariz; Dara Rizkya Aura; Nanda Arulia; Munira Munira (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: The andaliman fruit, scientifically known as Zanthoxylum acanthopodium is a traditional spice rich in essential oils. The fruit chemicals including alkaloids, flavonoids, steroids, tannins, and saponins, providing antibacterial potential. Chemical composition is influenced by environmental factors such as light exposure, temperature fluctiotions, pH levels, altitude, and humidity. The Gayo Highlands in Aceh Province have a significant influence on the chemical composition of plant due to their altitude and typical tempteratures.Objectives: This research aims to formulate andaliman fruit extract which grows in the Gayo Highlands into an antibacterial cream preparation and test its antibacterial activity.Methods: This research is experimental by making extracts, formulating andaliman fruit extract cream (0%, 2%, 3,5%, 5%, and 6,5%). Carrying out evaluation of cream preparations includes organoleptic examination, homogeneity test, pH examination and antibacterial test. The bacterial inhibitory power was analyzed using the Anova test and followed by the Duncan test.Results: The results of the preparation evaluation show that andaliman fruit extract cream meets all the criteria as a cream preparation where the pH ranges from 5,6 – 6,8. The findings of the antibacterial test proved the significant impact of the andaliman fruit cream from the Gayo highlands in inhibiting the growth of Staphylococcus aureus (P= 0,000).Conclusion: Cream preparations extract of andaliman fruit, it was concluded that all formulations met the evaluation criteria for cream preparations. The substantial diameter of the inhibition zone indicates the potential of the cream as an effective antibacterial.